Analisis Pengaruh Inovasi Digital Banking Terhadap Loyalitas Nasabah Di Wilayah Sidoarjo - Andre Rizky Rayhan Ubaidillah; Davin Al Aufa Setiawan; Ida Ayu Nuh Kartini (CV. SINAR HOWUHOWU, 2026)
The rapid advancement of information technology has accelerated digital transformation in the banking industry through the development of digital banking services, particularly mobile banking. Banks continuously introduce digital innovations to provide customers with more convenient, efficient, secure, and accessible financial services. However, increasing competition among banks and the emergence of financial technology (fintech) services require banking institutions to continuously innovate in order to maintain customer loyalty. At the same time, issues such as system disruptions, limited application features, and transaction security concerns may affect customers' experiences and loyalty. This study aims to analyze digital banking innovation in improving customer loyalty among mobile banking users in Sidoarjo Regency. The study employs a qualitative descriptive approach. Informants are selected using purposive sampling, consisting of active mobile banking users residing in Sidoarjo Regency. Data are collected through in-depth interviews, observation, and documentation, and are analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. Data validity is ensured through source and technique triangulation. This study is expected to provide a comprehensive understanding of digital banking innovations perceived by customers and explain how these innovations contribute to strengthening customer loyalty. The findings are expected to serve as a reference for banking institutions in developing more innovative, secure, and customer-oriented digital banking services.